Characteristics of ice-nucleating particles in Beijing during spring: A comparison study of measurements between the suburban and a nearby mountain area. (15th January 2023) - Hu, Yaqiong; Tian, Ping; Huang, Mengyu; Bi, Kai; Schneider, Julia; Umo, Nsikanabasi Silas; Ullmerich, Nikolas; Höhler, Kristina; Jing, Xiaoqin; Xue, Huiwen; Ding, Deping; Liu, Yongchun; et al.
Abstract: Ice-nucleating particles (INPs) are of great importance for regional weather and climate by altering the microphysical properties of clouds. However, large uncertainties still exist for INP concentrations over the polluted North China Plain (NCP) due to limited INPs observation in this region and the complex physical and chemical properties of aerosols from multiple sources. In this study, the concentrations of INPs active in the immersion freezing mode at temperatures ranging from −5 °C to −30 °C are simultaneously measured for about one month in the Spring season at a mountain site and a suburb site in Beijing representing clean and anthropogenic condition, respectively. Different concentrations and characteristics of INPs are found between the two sites, which reflect the influence of different air masses and INP sources. Consistent with previous studies in this region, dust particles are found to be the most efficient INPs during the Spring season, and the contribution of anthropogenic pollution aerosols was not obvious. Most interestingly, the INP concentration at the mountain site was about one magnitude higher than at the suburban site at temperatures warmer than −10 °C, which is caused by primary biological aerosol originating from the forest in the mountainous area. Our results underline the important role of these biological aerosols, which are also expected to have a strong impact on the glaciation of orographic clouds. Highlights: Meteorological conditions were the main influencing factor of INPs over Beijing. Mineral dusts were found to be the most efficient INPs sources during the Spring season. Primary biological aerosol particles from the northwest boreal forest area of Beijing might be an important INPs source.